ANALYSIS OF MAST CELL DENSITY IN NORMAL ORAL MUCOSA VS DIFFERENT GRADES OF ORAL SQUAMOUS CELL CARCINOMA - Gupta, Sandeep; Misurya, Rajat; Misurya, Archana; Singh , Harkanwal Preet (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND-Mast cells display a diversity of roles in extracellular matrix degradation, angiogenesis and innate and purchased immune responses, thanks to their ability to release a variety of pre-formed mediators, including cytokines, vasoactive amines, and enzymes on activation. Angiogenesis or neovascularization is crucial for development and progression of malignant tumors. This biologic process is regulated by angiogenic factors, like basic fibroblast protein (bFGF), vascular endothelial protein (VEGF), tumor necrosis factor-α (TNF-α), and angiogenic inhibitors, like angiostatin, platelet coagulation factor (PF4) and thrombospondin-1 (TSP-1).2,3 These factors are released by tumoral and stromal cells.MATERIALS AND METHODS-Formalin-fixed, paraffin embedded tissue specimens of 60 cases of OSCC were retrieved and divided into group 1-3 (20 poorly differentiated OSCC, 20 moderately differentiated OSCC, and 20 well differentiated OSCC). Twenty normal oral tissues of patients without any habits were included in the study, and they were selected as controls. Along with the H&E stained sections, another set of the same tissues were processed and stained with 1%Toluidine blue. 5 μm sections of formalin-fixed, paraffin blocks were deparaffinized with xylene and they were rehydrated with graded alcohols. RESULTS-Mean Mast Cell Density in Different Histological Grades of OSCC and Normal Mucosa were calculated. Group1 shows the mean Average Mast Cell (4.15±1.46), Group2 shows the mean Average Mast Cell (7.10±2.29), Group 3 shows the mean Average Mast Cell (9.35±1.72), Group 4 shows the mean Average Mast Cell (3.35±1.69).CONCLUSION-The effect of mast cells on prognosis could not be assessed in this study as time lapse between biopsy and treatment and further follow up was too less to quantify. However larger samples and large scale multi-institutional studies could provide a baseline data of MCD in different grades of OSCC. Along with this,recurrent cases and follow up studies over long periods of time like 1 – 10 years are required to validate the role and quantification of the MCD in high risk and low risk individuals, role in prognosis predilection, in planning and development of various adjuvant therapeutics strategies.